Contents - Ελληνική Ψυχολογική Εταιρεία ΕΛΨΕ (Psychology: the Journal of the Hellenic Psychological Society, 2018)
SPECIAL SECTION «EMOTIONS: THEORY, RESEARCH AND APPLICATIONS» Guest editor: Antonia Papastylianou